THE SELECTION OF INFORMATION-MEASURING MEANS FOR THE ROBOTOTECHNICAL COMPLEX AND THE RESEARCH OF THEIR WORKER CHARACTERISTICS - Mammadov, J. F.; Ahmadova, T. A.; Huseynov, A. H.; Talibov, N. H.; Hashimova, H. M.; Ahmadov, A. A. (Radio Electronics, Computer Science, Control, 2025)
Context. The topic of the article is devoted to the issue selection of the means of the information-measurement system (IMS) for automation of robototechnical complexes (RTC) of flexible production systems applied in various fields of industry, and the research of their technological characteristics. Objective. The goal is using the mathematical models to researching of the working characteristics of the new construction transmitters for information – measurement and automated control of robototechnical complex in flexible production areas. Method. In the article, the following issues were set and solved: the analysis of the application object, the selection of the types of information-measurement and management elements of RTC creation and structure scheme; research of the characteristics of the information-measuring transmitter for managing the active elements of the RTC; determining the error of the analog output transmitter of the information-measurement system of RTC active elements. Based on the analysis of the application object, it was determined that the structure scheme of the RTC at the flexible production system includes complex technological, functionally connected production areas, modules and robotic complexes, their automated control system IMS, regulation, execution, microprocessor control system and devices and devices of the industrial network. includes The functional block diagrams of the IMS of RTCi of the flexible production system are given. Based on research, it was found that it is convenient to use a magnetoelastic transducer with a ring sensitive element to measure the mechanical force acting on the working organs of an industrial robot (IR). For this, unlike existing transmitters, the core of this transmitter is made of whole structural steel. The inductive coil of the proposed transmitter is included in the LC circuit of the autogenerator. The magnetoelastic emitter semiconductor is assembled at the base of the transistor. The crosssection of its core is calculated for the mechanical stress that can be released for the steel. The block-scheme of the inductive transmitter is proposed. The proposed transmitters work on the principle of an autogenerator assembled on an operational amplifier. A mathematical expression is defined for determining the output frequency of the autogenerator. The model of the autogenerator consists of a dependent source, the transmission coefficient is determined. Results. A new transmitter is proposed to measure the information of the manipulator to perform special technological operations synchronously. Conclusions. A mathematical model was developed to determine the error of the analog output transmitter of the informationmeasurement system of RTC active elements. The expression ehq is used to determine the error of the transmitter whose output is analog during the measurement of the current technological operation. It was determined that in practice, the geometric dimensions of the transmitter and the number of windings remain unchanged during the work process, where it is changed due to the influence of the environment. Considering this variation, a mathematical model was developed to determine the transmitter error.